HASIL VALIDITAS PENGEMBANGAN BAHAN AJAR BERGAMBAR DISERTAI PETA KONSEP UNTUK PEMBELAJARAN BIOLOGI SMA SEMESTER 1 KELAS XI - Meiriza Suswina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
Among the competences expected from teachers as stated in School-based Curriculum (KTSP) is the ability to develop instructional materials which are suitable with the students. However, the implementation shows that teachers still find it difficult to design and develop instructional materials. One of the ways is to develop instructional materials with picture and concept maps. This research was aimed at developing valid instructional materials. It was expected that those materials improve students’ comprehension toward biology concepts. This research employed Research and Development design which used 4-D (Four-D) Model. This model consisted of defining, designing, developing and disseminating. Data for the determination of the validity of Instructional materials were obtained from validity checklist. Validity included such aspects as 1) material, 2) presentation and 3) language and readability. The findings showed that instructional materials with picture and concept maps were valid. Specifically, the scores for such aspects as 1) material, 2) presentation and 3) language and readability were 3.36, 3.48, and 3.37 respectively.Kata kunci: validitas bahan ajar bergambar, peta konsep untuk pembelajaran biologi